Strengthening Community Media Literacy and Digital Skills through Smart Media Education in Talang Pasak Village, North Bengkulu Regency - Parwito Parwito; Wismalinda Rita; M. Rafhel Anggra Setia; Tri Wahyuniarti (JURNAL BESEMAH, 2026)
The rapid development of digital technology has transformed how people access, produce, and disseminate information through various media platforms. While easier access to digital media provides numerous benefits, it also increases the risk of exposure to hoaxes, disinformation, online fraud, privacy violations, and unethical or irresponsible social media use. These challenges highlight the importance of strengthening media literacy and digital skills, particularly among rural communities. This community service program aimed to improve community knowledge, critical awareness, and digital skills in using digital media intelligently, safely, ethically, and responsibly in Talang Pasak Village, Kerkap District, North Bengkulu Regency. The program employed educational, participatory, and contextual approaches through several stages, including needs identification, educational sessions, interactive discussions, simulations for identifying and verifying digital information, safe digital media practices, evaluation, and reflection. The educational materials covered media and digital literacy, identification of credible information and hoaxes, personal data protection, ethical communication on social media, and productive use of digital platforms. The results indicated positive improvements in participants’ understanding and responses, particularly in recognizing information that requires verification, understanding the importance of protecting personal data, and applying ethical principles when interacting in digital spaces. Participants also demonstrated active engagement in discussions and case-based simulations related to everyday social media use. These findings indicate that education based on real-life digital challenges and practical activities can serve as an appropriate strategy for strengthening media literacy and digital skills in rural communities. The sustainability of the program requires continuous assistance, accessible educational resources, and active collaboration between village authorities and community members to foster a critical, safe, productive, ethical, and responsible digital culture.